Targeting aid to the needy and deserving: nothing but promises? - Peter Nunnenkamp; Gustavo Canavire-Bacarreza; Luis Trive\~no (Kiel Institute for World Economics (IfW), 2004)
By reallocating aid to where it is needed most and where a productive use is most likely, donors could help alleviate poverty in developing countries. The rhetoric of donors suggests that this insight has increasingly shaped the allocation of aid. However, we find little evidence supporting the view that the targeting of aid has improved significantly. Most donors provide higher aid to relatively poor countries, but so far the fight against poverty has not resulted in a stronger focus on recipient countries with particularly high incidence of absolute poverty. Many donors failed to direct aid predominantly to where local conditions were conducive to a productive use of inflows. The response of donors to changing institutional and policy conditions in recipient countries turns out to be fairly weak. In particular, we reject the proposition that multilateral donor institutions provide better targeted aid than bilateral donors.
Keywords: F35; 330; bilateral aid; multilateral aid; poverty; economic policy assessment; quality of institutions; Entwicklungshilfe; Entwicklungskooperation; Armutspolitik; Wirtschaftspolitische Wirkungsanalyse; Entwicklungsländer